Accelerating drug development for neuroblastoma: Summary of the Second Neuroblastoma Drug Development Strategy forum from Innovative Therapies for Children with Cancer and International Society of Paediatric Oncology Europe Neuroblastoma. (September 2020) - Moreno, Lucas; Barone, Giuseppe; DuBois, Steven G.; Molenaar, Jan; Fischer, Matthias; Schulte, Johannes; Eggert, Angelika; Schleiermacher, Gudrun; Speleman, Frank; Chesler, Louis; Geoerger, Birgit; Hogarty, Michael D.; et al.
Abstract: Only one class of targeted agents (anti-GD2 antibodies) has been incorporated into front-line therapy for neuroblastoma since the 1980s. The Neuroblastoma New Drug Development Strategy (NDDS) initiative commenced in 2012 to accelerate the development of new drugs for neuroblastoma. Advances have occurred, with eight of nine high-priority targets being evaluated in paediatric trials including anaplastic lymphoma kinase inhibitors being investigated in front-line, but significant challenges remain. This article reports the conclusions of the second NDDS forum, which expanded across the Atlantic to further develop the initiative. Pre-clinical and clinical data for 40 genetic targets and mechanisms of action were prioritised and drugs were identified for early-phase trials. Strategies to develop drugs targeting TERT, telomere maintenance, ATRX, alternative lengthening of telomeres (ALT), BRIP1 and RRM2 as well as direct targeting of MYCN are high priority and should be championed for drug discovery. Promising pre-clinical data suggest that targeting of ALT by ATM or PARP inhibition may be potential strategies. Drugs targeting CDK2/9, CDK7, ATR and telomere maintenance should enter paediatric clinical development rapidly. Optimising the response to anti-GD2 by combinations with chemotherapy, targeted agents and other immunological targets are crucial. Delivering this strategy in the face of small patient cohorts, genomically defined subpopulations and a large number of permutations of combination trials, demands even greater international collaboration. In conclusion, the NDDS provides an internationally agreed, biologically driven selection of prioritised genetic targets and drugs. Improvements in the strategy for conducting trials in neuroblastoma will accelerate bringing these new drugs more rapidly to front-line therapy. Highlights: The Neuroblastoma New Drug Development Strategy initiative aims to accelerate new drugs development. Twenty two of 40 targets were identified as high priority for neuroblastoma. Targeting telomere maintenance, ATRX, BRIP1, RRM2 are high priority for drug discovery. Drugs targeting CDK2/9, CDK7, ATR should enter paediatric clinical development rapidly. Combining targeted therapies with immunological agents is crucial.